2022
DOI: 10.3389/fmed.2022.854184
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Analysis of Choroidal Vessels in the Eyes of Patients With Unilateral BRVO

Abstract: PurposeTo investigate the three-dimensional analysis of choroidal vascular changes in eyes with monocular branch retinal vein occlusion (BRVO) using swept-source optical coherence tomography (SS-OCT).MethodsTwenty two unilateral BRVO patients with superior-temporal branch retinal vein occlusion and 27 healthy eyes were analyzed retrospectively. OCT and OCT angiography (OCTA) images of 12 * 12 mm centered on the foveal of each eye were analyzed. Three-dimensional choroidal vascularity index (CVI), choroidal thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“… 9 , 42 , 43 Nevertheless, other studies found similar CC-VFD in CRVO and BRVO eyes compared to their respective fellow eyes. 15 , 44 In our analysis using UWF-SS-OCTA, no differences were observed in CC-VFD in ischemic CRVO and BRVO eyes compared to their fellow eyes and control eyes. Although the reasons for the discordant findings regarding the choroid in RVO among these various studies are not well understood, we speculate that differences in gender, axial length, type and stage of RVO, and RVO-associated complications such as ME may play a role.…”
Section: Discussionmentioning
confidence: 58%
“… 9 , 42 , 43 Nevertheless, other studies found similar CC-VFD in CRVO and BRVO eyes compared to their respective fellow eyes. 15 , 44 In our analysis using UWF-SS-OCTA, no differences were observed in CC-VFD in ischemic CRVO and BRVO eyes compared to their fellow eyes and control eyes. Although the reasons for the discordant findings regarding the choroid in RVO among these various studies are not well understood, we speculate that differences in gender, axial length, type and stage of RVO, and RVO-associated complications such as ME may play a role.…”
Section: Discussionmentioning
confidence: 58%
“…As for the correlation analyses between 2D CVI and 3D CVI across various combinations of participant groups and time points, while 3D CVI has been used in the evaluation of choroidal angioarchitecture in nonuveitic diseases such as retinitis pigmentosa 18 , central serous chorioretinopathy 19, , branch retinal vein occlusion 21 , none of these published studies has studied the correlation between 2D subfoveal CVI and 3D volume CVI, let alone such a correlation in that of uveitis. Thus, to the best of our knowledge, our current study is the rst to reveal the correlation between 2D subfoveal CVI and 3D CVI in uveitis, and more broadly, any pathological state.…”
Section: Discussionmentioning
confidence: 99%
“…However, B-scan is a single cross-sectional image and cannot fully reflect the overall vascular structure changes of the choroid. Some researchers have used B-scan images to form three-dimensional reconstructions of choroidal vessels for CVI calculation, which represents the volumetric choroidal density and may more comprehensively reflect the ratio of CVI in a particular region compared to cross-sectional images [ 42 ]. In the sub-analysis based on the study area, two studies [ 37 , 40 ] used the three-dimensional method, and WMD in this subgroup was lower than the macular subgroup ( Fig 8E ).…”
Section: Discussionmentioning
confidence: 99%